Improving Dewaterability and Other Properties of Citric Acid Wastewater Treatment Sludge by Ozone and Peroxone. (2nd January 2020) - Ding, Ning; Peng, Can; Liu, Hong; Ren, Yuxiao; Wang, Xiao; Wang, Ping; Dong, Liming; Hu, Xiuyu
ABSTRACT: The efficacies of ozonation and peroxone (O3 /H2 O2 ) pretreatments were compared for citric acid wastewater sludge conditioning with the objective of improving dewatering characteristics of the sludge. Treatment with 84 mg O3 /g dry solid (DS) and 12.5 mg/g DS H2 O2 greatly enhanced the effectiveness of ozonation, providing sludge dewaterability similar to that obtained by ozonation at 250 mg O3 /g DS. Most importantly, treatment of citric acid wastewater sludge with 84 mg O3 /g DS and 12.5 mg/g DS H2 O2 led to the preservation of the nutrient elements nitrogen, phosphorus, and potassium in the sludge with a minimal volatile suspended solids/total suspended solids reduction of 5.5%, which is much lower than that with ozonation at 250 mg O3 /g DS.